Correlation between Driving Behavior and Brain Activity during Turning Revealed by a Simulated Driving Experiment. Issue 1 (1st April 2022) - Zhang, Jiawen; Chen, Yuan; Cheng, Yu; Shi, Changcheng; Wu, Yibo; Yan, Lirong
Abstract: Driving behavior during turning is influenced by the driver's cognitive state and decision-making ability, which are tightly related with the brain activity, but the relationship mechanism is rather complex and has not been fully studied. In this paper, a fusion analysis method of electroencephalography (EEG) and driving data was proposed to explore this correlation. The subjects were divided into three groups, namely the conservative group, moderate group and the aggressive group by k-means++ algorithm. The results of Statistical Parameter Mapping (SPM) showed that the temporal and the frontal regions of all subjects were found to be activated during turning, which meant that driving behavior was associated with attention, decision-making and executive control. Compared with the moderate group, the activation intensity of the frontal lobe, temporal lobe and the posterior central gyrus of the conservative group was higher, while the intensity of the superior temporal gyrus, calcarine cortex and the lingual gyrus decreased, indicated that they need more resources to process cognitive tasks such as hearing and vision, thereby showing more conservative driving behavior; The aggressive group had stronger activity in the middle temporal gyrus and the inferior temporal gyrus, while the activity decreased in the calcarine cortex, middle frontal gyrus, paracentral lobule, posterior central gyrus and the precuneus, which indicated that they were easy to performed aggressive driving behavior due to their poor risk prediction ability and higher cognitive load during turning.